2020
DOI: 10.3390/biomedicines8100410
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Alterations in Multiple Sclerosis Show Increased Proinflammatory Potential

Abstract: Multiple sclerosis (MS) is an inflammatory autoimmune disorder affecting the central nervous system (CNS), with unresolved aetiology. Previous studies have implicated N-glycosylation, a highly regulated enzymatic attachment of complex sugars to targeted proteins, in MS pathogenesis. We investigated individual variation in N-glycosylation of the total plasma proteome and of IgG in MS. Both plasma protein and IgG N-glycans were chromatographically profiled and quantified in 83 MS cases and 88 age- and sex-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
2
30
1
1
Order By: Relevance
“…Like the tuSz 1 mutant, the αM-II mouse phenotype arises due to alterations in protein N-glycosylation in nonimmune tissues and is mediated by innate immune cells (115). Altered patterns of protein N-glycosylation are also observed in additional mouse models of autoimmune disease (117,118) and have been linked to autoimmune disease in human patients (119)(120)(121)(122)(123).…”
Section: Discussionmentioning
confidence: 99%
“…Like the tuSz 1 mutant, the αM-II mouse phenotype arises due to alterations in protein N-glycosylation in nonimmune tissues and is mediated by innate immune cells (115). Altered patterns of protein N-glycosylation are also observed in additional mouse models of autoimmune disease (117,118) and have been linked to autoimmune disease in human patients (119)(120)(121)(122)(123).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a variety of autoimmune and inflammatory diseases such as autoimmune hemolytic anemia, systemic lupus erythematosus, inflammatory bowel disease, and rheumatoid arthritis have skewed IgG glycosylation pattern, 6‐9 and in some diseases, the skewed IgG glycosylation is associated with disease severity and treatment response 10,11 . In addition to IgG, the altered glycosylation pattern of total serum proteins, which is considered reflecting the physiological and pathological state of the body, is also associated with autoimmune and inflammatory diseases 12 12‐16 …”
Section: Introductionmentioning
confidence: 99%
“…The basic characteristics of the cohorts are given in Table 1. IgG glycosylation was analysed using a well-established reliable liquid chromatography method for IgG N-glycan analysis with con rmed reproducibility and robustness 30,31 , and which has already been successfully employed to detect signi cant changes in glycosylation in many different diseases (such as COVID-19 32 , thyroid disease 33 , multiple sclerosis 34 , rheumatoid arthritis 35 , cardiovascular disease 36 and systemic lupus erythematosus 37 ). IgG glycans were separated into 24 chromatographic peaks (GP1-GP24) and glycans corresponding to each individual peak are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%